Diabetes and breast cancer risk: a meta-analysis - Boyle, P; Boniol, M; Koechlin, A; Robertson, C; Valentini, F; Coppens, K; Fairley, L-L; Boniol, M; Zheng, T; Zhang, Y; Pasterk, M; Smans, M; et al. (Breast cancer research and treatment, 2012)
Background: The potential of an increased risk of breast cancer in women with diabetes has been the subject of a great deal of recent research. Methods: A meta-analysis was undertaken using a random effects model to investigate the association between diabetes and breast cancer risk. Results: Thirty-nine independent risk estimates were available from observational epidemiological studies. The summary relative risk (SRR) for breast cancer in women with diabetes was 1.27 (95% confidence interval (CI), 1.16–1.39) with no evidence of publication bias. Prospective studies showed a lower risk (SRR 1.23 (95% CI, 1.12–1.35)) than retrospective studies (SRR 1.36 (95% CI, 1.13–1.63)). Type 1 diabetes, or diabetes in pre-menopausal women, were not associated with risk of breast cancer (SRR 1.00 (95% CI, 0.74–1.35) and SRR 0.86 (95% CI, 0.66–1.12), respectively). Studies adjusting for body mass index (BMI) showed lower estimates (SRR 1.16 (95% CI, 1.08–1.24)) as compared with those studies that were not adjusted for BMI (SRR 1.33 (95% CI, 1.18–1.51)). Conclusion: The risk of breast cancer in women with type 2 diabetes is increased by 27%, a figure that decreased to 16% after adjustment for BMI. No increased risk was seen for women at pre-menopausal ages or with type 1 diabetes.